2020
DOI: 10.1111/echo.14925
|View full text |Cite
|
Sign up to set email alerts
|

Impaired left atrial stiffness in patients with corrected congenital left ventricular outflow obstructions

Abstract: Objective We examined the left atrial stiffness index (LA Stiff) on echocardiography and its determinants in adults and adolescents with repaired congenital left ventricular outflow obstructions (c‐LVOOs), including isolated subaortic stenosis (SAS), stenotic bicuspid aortic valve (BAV), and aortic coarctation (CoA). Methods Seventy‐two patients (43 males, age: 31 ± 15 years) with repaired c‐LVOOs (SAS: n = 12; BAV: n = 27; CoA: n = 33) were compared to 72 age‐ and sex‐matched controls. 2D strain imaging was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Normalizing LA strain to estimated filling pressures ( E / e ′) may be more acurate to detect elevated filling pressure in the specific population of cTOF in whom standard parameters were reported to be less performant compared to general population ( 35 ). Our findings are in keeping with previous studies having demonstrated the potential interest of another combined echocardiographic parameters including LA stiffness estimated with the ratio ( E / E ′)/LAS ( 36 , 37 ). LA stiffness was shown to be accurate in providing important information on LA function as well as a prognostic factor ( 34 ).…”
Section: Discussionsupporting
confidence: 92%
“…Normalizing LA strain to estimated filling pressures ( E / e ′) may be more acurate to detect elevated filling pressure in the specific population of cTOF in whom standard parameters were reported to be less performant compared to general population ( 35 ). Our findings are in keeping with previous studies having demonstrated the potential interest of another combined echocardiographic parameters including LA stiffness estimated with the ratio ( E / E ′)/LAS ( 36 , 37 ). LA stiffness was shown to be accurate in providing important information on LA function as well as a prognostic factor ( 34 ).…”
Section: Discussionsupporting
confidence: 92%